Entrepreneurship development program for afrocolombian women displaced by political and economical violence (2010)
The Colombian government and some nongovernmental organizations (NGO) are interested in helping women who have been victims of forced displacement, by the violence in Colombia, to develop entrepreneurial activities that will help them to improve family income and in that way reinsert them in the social tissue. These institutions were not ready to provide the required training and for that reason they contacted the Centre for Entrepreneurship Development at Universidad Icesi to design and implement a program specifically oriented to them. This article describes the process, the variables, the difficulties, the activities, the learned lessons and some results when a specific program for afrocolombian women was implemented. The experience confirms Gibb idea that there is not unique solutions in entrepreneurship education and that every program has to consider very carefully the characteristics of the population to be covered and the conditions of the environment.